PENGEMBANGAN MODUL P5 (PROJEK PENGUATAN PROFIL PELAJAR PANCASILA) DENGAN PEMANFAATAN LIKURANG (LIMBAH KULIT KERANG) DALAM UPAYA PENINGKATKAN KEMAMPUAN INKUIRI MELALUI EKPLORASI BUDAYA DAN LINGKUNGAN - Dara Fitrah Dwi; Muhammad Faisal Husna; Dalimawaty Kadir; Novita Friska (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop a P5 module (project for strengthening the Pancasila student profile) using LiKuRang (shell waste) to improve students’ inquiry skills through cultural and environmental exploration. This research employed a research and development method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were elementary school students in Tanjungbalai City. Data were collected using module and material expert validation sheets, teacher response questionnaires, student response questionnaires, and inquiry skill assessment instruments. The data were analyzed using descriptive statistics. The results showed that the LiKuRang-based P5 module was categorized as very feasible, with a score of 100% from module experts and 84% from material experts. Teacher responses indicated a very feasible category with a score of 100%, while student responses reached 96.5%, also categorized as very feasible. The implementation of the LiKuRang-based P5 module was able to enhance students’ inquiry skills, particularly in observing, questioning, collecting data, and drawing conclusions through cultural and environmental exploration. This study contributes to the development of contextual teaching materials based on local wisdom that support the strengthening of the Pancasila student profile and meaningful learning in elementary schools.